Exploring utility, attitude, intention to use, satisfaction, and loyalty in B2C/P2P car-sharing economy - Lee, Sunme,Cho, Yoon Cheong (KDI School of Public Policy and Management, 2015)
The sharing economy, facilitated by technology and social media, has grown rapidly across the world. The sharing economy is still in a fledgling phase, so relatively little research has been carried out on it. By classifying the existing and potential users, the purpose of the study is to investigate effects of perceptions on utilities, attitude, satisfaction, loyalty, and intention to use for both cases of B2C and P2P car-sharing. Study 1 examines the effects of the level of utility related to the levels of satisfaction and loyalty to existing users and intentions to use and expected satisfaction to potential users of B2C car-sharing, while Study 2 investigates the effects of their intention and levels of expected satisfaction to potential users of P2P car-sharing. This study collected the data via online and offline survey and applied statistical analyses including factor analysis, regression analysis, and ANOVA. The results revealed that the effect of perceived utilities on attitude differ for existing and potential users, and also for cases of B2C and P2P car-sharing. The findings of this study have provided managerial, theoretical, and policy implications
10.2139/ssrn.2707857
Keywords: Graue Literatur; Sharing Economy; Car-sharing; Utility; Attitude; Intention; Satisfaction; Loyalty